2004
DOI: 10.1293/tox.17.245
|View full text |Cite
|
Sign up to set email alerts
|

A New Screening Model Using F1(AWE * WE) Japanese Quail Embryo for Evaluating Sex Reversal Effects

Abstract: F 1 (AWE × WE) strain of Japanese quail (Corturnix japonica) is produced from a mating between male AWE (albino plumage color) and female WE (wild plumage color) strains of Japanese quail. Male and female offspring exhibit wild and albino plumage colors, respectively, ruled by a criss-cross inheritance. F 1 (AWE × WE) eggs received 17 beta-estradiol (E 2 ) or methyltestosterone (MT) at 0, 20, 200, 2000, and 20000 ng/egg just before incubation. At 16 days of incubation, embryos were subjected to a complete necr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 17 publications
3
13
0
Order By: Relevance
“…Previous workers did not find significant effects of in ovo treatment with androgenic compounds on the behavior, morphology, or sexual differentiation of the Japanese quail (Schumacher et al, 1989;Shibuya et al, 2004). Recently, however, Quinn et al (2007a,b) demonstrated that the in ovo treatment of 0.05 to 50 μg of trenbolone acetate, a synthetic androgen, on d 4 of incubation resulted in the inhibition of cloacal gland development and smaller and fewer follicles of bursa of Fabricius in male adult Japanese quail.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Previous workers did not find significant effects of in ovo treatment with androgenic compounds on the behavior, morphology, or sexual differentiation of the Japanese quail (Schumacher et al, 1989;Shibuya et al, 2004). Recently, however, Quinn et al (2007a,b) demonstrated that the in ovo treatment of 0.05 to 50 μg of trenbolone acetate, a synthetic androgen, on d 4 of incubation resulted in the inhibition of cloacal gland development and smaller and fewer follicles of bursa of Fabricius in male adult Japanese quail.…”
Section: Discussionmentioning
confidence: 91%
“…Schumacher et al (1989) reported that the exposure with 5β-dihydrotestosterone on d 9 of incubation in Japanese quail eggs showed no effect on behavior and morphology in male adults derived from the treated eggs. Shibuya et al (2004) treated fertile quail eggs with methyl testosterone just before incubation, but failed to find any effect on the sexual differentiation and structures of testes or ovaries in 16-d-old embryos. Recently, Quinn et al (2007a,b) demonstrated that the in ovo treatment with trenbolone acetate, an androgenic compound, on d 4 of incubation resulted in the inhibition of cloacal gland development and smaller and fewer follicles of bursa of Fabricius in male adult Japanese quail.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…The compounds were injected into the egg white through a small hole punched with a sterilized disposable 25-gauge needle at the blunt end of the egg, using a sterilized disposable 27-gauge needle attached to a sterilized Hamilton syringe as described previously [8]. The compounds were injected into the egg white through a small hole punched with a sterilized disposable 25-gauge needle at the blunt end of the egg, using a sterilized disposable 27-gauge needle attached to a sterilized Hamilton syringe as described previously [8].…”
Section: Methodsmentioning
confidence: 99%
“…A mating between male AWE quail with albino plumage color (AL Ã A/AL Ã A) and female WE quail with wild plumage color (AL Ã N/W) produced inheritably male F 1 quail with wild plumage color (AL Ã N/AL Ã A) and female F 1 quail with albino plumage color (AL Ã A/W) ruled by a criss-cross inheritance as described previously [8,9] (Fig. A mating between male AWE quail with albino plumage color (AL Ã A/AL Ã A) and female WE quail with wild plumage color (AL Ã N/W) produced inheritably male F 1 quail with wild plumage color (AL Ã N/AL Ã A) and female F 1 quail with albino plumage color (AL Ã A/W) ruled by a criss-cross inheritance as described previously [8,9] (Fig.…”
Section: Parent Strains Of Japanese Quailmentioning
confidence: 99%